2006
DOI: 10.1074/jbc.m601350200
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitors Induce Death but Activate NF-κB on Endometrial Carcinoma Cell Lines and Primary Culture Explants

Abstract: Proteasome inhibitors are currently used as chemotherapeutic drugs because of their ability to block NF-B, a transcription factor constitutively activated in many different types of human cancer. In the present study, we demonstrate that proteasome inhibitors induce cell death in endometrial carcinoma cell lines and primary explants but, instead of blocking NF-B, they increase its transcriptional activity. Proteasome inhibitors induce phosphorylation of IKK␣/␤, phosphorylation and degradation of IB␣, and phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 39 publications
9
68
1
Order By: Relevance
“…Interestingly, there have been several reports that proteasome inhibitors activate transcription factor NF-B in certain cell types (63)(64)(65)(66), and NF-B has been shown to inhibit Col-I ␣1 promoter activity (67).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there have been several reports that proteasome inhibitors activate transcription factor NF-B in certain cell types (63)(64)(65)(66), and NF-B has been shown to inhibit Col-I ␣1 promoter activity (67).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that NF-κB activation could result in transcription of some antiapoptotic genes, such as Bcl-xl (41)(42)(43), one of the antiapoptotic Bcl-2 family proteins responsible for mitochondrial membrane permeabilization. Our results showed that Bcl-xl protein was expressed at significantly higher levels in A549 cells induced with Taxol, whereas expression of Bcl-xl was reduced when cells were treated with parthenolide in combination with Taxol through down-regulation of NF-κB signaling, effects that paralleled their synergistic toxicity in A549 cancer cells.…”
Section: Parthenolide Potentiates Chemosensitizationmentioning
confidence: 99%
“…However, this result is actually consistent to the finding in endometrial carcinoma cell lines in which PS-341 induces IkBa degradation albeit with induction of cell death. 27 Since the combination of PS-341 and DTX exerts consistent results on decreasing IkBa levels, but generates opposite biological outcomes in inducing cell death in A549 and H1792 cell lines, it appears that modulation of IkBa and NFkB signaling pathway cannot account for their different biological outcomes.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%